2011
DOI: 10.1093/sleep/34.1.111
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of CPAP in Normalizing Daytime Sleepiness, Quality of Life, and Neurocognitive Function in Patients with Moderate to Severe OSA

Abstract: Our study suggests that a greater percentage of patients achieve normal functioning with longer nightly CPAP duration of use, but a substantial proportion of patients will not normalize neurobehavioral responses despite seemingly adequate CPAP use. It is thus crucial to adequately assess patients after CPAP therapy and seek alternate etiologies and treatments for any residual abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
255
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 446 publications
(277 citation statements)
references
References 27 publications
18
255
1
3
Order By: Relevance
“…15 Signifi cant improvements in objective and subjective sleepiness, blood pressure (BP), QOL, and neurocognitive function are noted with CPAP use. [15][16][17] Furthermore, treatment of severe OSA with CPAP reduces the risk of cardiovascular events.…”
mentioning
confidence: 99%
“…15 Signifi cant improvements in objective and subjective sleepiness, blood pressure (BP), QOL, and neurocognitive function are noted with CPAP use. [15][16][17] Furthermore, treatment of severe OSA with CPAP reduces the risk of cardiovascular events.…”
mentioning
confidence: 99%
“…In other previous studies, a dose-response effect on ESS scores was documented after 3 months of CPAP treatment. 22,23 In another earlier study, Pietrzyk et al 24 found a beneficial effect of 1 y of CPAP treatment on excessive daytime sleepiness in subjects with OSA. Our findings were compatible with previous studies and also supported the dose-dependent response of excessive daytime sleepiness to long-term CPAP treatment.…”
Section: Daytime Sleepiness and Cpapmentioning
confidence: 95%
“…sleepiness [3], and snoring, but a reduction in hypertension [4], car accidents [5,6] and mortality [7] is also seen in patients compliant with therapy. In addition, CPAP has shown itself to be a cost effective treatment option compared to lifestyle measures [8] There is a wide range of CPAP compliance rates reported in the literature, varying by study design and definitions of compliance, with values ranging from 46 % to 85 % [9,10].…”
Section: Introductionmentioning
confidence: 99%